2008
DOI: 10.1172/jci33249
|View full text |Cite
|
Sign up to set email alerts
|

Sustained activation and tumor targeting of NKT cells using a CD1d–anti-HER2–scFv fusion protein induce antitumor effects in mice

Abstract: Invariant NKT (iNKT) cells are potent activators of DCs, NK cells, and T cells, and their antitumor activity has been well demonstrated.A single injection of the high-affinity CD1d ligand α-galactosylceramide (αGalCer) leads to short-lived iNKT cell activation followed, however, by long-term anergy, limiting its therapeutic use. In contrast, we demonstrated here that when αGalCer was loaded on a recombinant soluble CD1d molecule (αGalCer/sCD1d), repeated injections led to sustained iNKT and NK cell activation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(83 citation statements)
references
References 46 publications
5
73
5
Order By: Relevance
“…Several studies have shown improved antitumor activity of iNKT cells with the use of various tools or materials (24,25). In our study, ␣GC-mediated antitumor effect was significantly increased by administration of anti-PD-1 mAb at the time of ␣GC treatment.…”
Section: Resultssupporting
confidence: 47%
“…Several studies have shown improved antitumor activity of iNKT cells with the use of various tools or materials (24,25). In our study, ␣GC-mediated antitumor effect was significantly increased by administration of anti-PD-1 mAb at the time of ␣GC treatment.…”
Section: Resultssupporting
confidence: 47%
“…Furthermore, as repeated i.v. administration of a-GalCer induces iNKT cell anergy and repeated administration of CD1d-targeted constructs results in sustained iNKT cell activation (29), tumor-targeting of iNKT cells or a-GalCer-pulsed APC might alternatively constitute a powerful yet unexplored clinical approach (5).…”
Section: Discussionmentioning
confidence: 99%
“…iNKT cells bridge the innate and adaptive arms of the immune system by producing a variety of cytokines very rapidly after stimulation (1,2). In view of their transactivating properties, iNKT cells have been implicated in autoimmunity, viral infection, and tumor immunity (1,4,5). During thymic development, iNKT cells are branched off from conventional T cells at double-positive (DP) stage (6).…”
Section: N Atural Killer T Cells Have Been Well Defined As a Uniquementioning
confidence: 99%